Encapsulation of albumin from snakehead fish (Channa striata) with porous starch from arrowroot (Maranta arundinacea) - Nastitia Dian Pratiwi; Arima Diah Setiowati; Lucia Dhiantika Witasari (Carbohydrate Polymer Technologies and Applications)
Through an enzymatic process, arrowroot (Maranta arundinacea) porous starch produces pores on the surface of starch granules, making it a potential bioadsorbent and encapsulation material. Snakehead fish albumin (Channa striata) is a sensitive component whose functional properties must be preserved. Therefore, encapsulating albumin through spray drying is necessary to protect it from external environmental factors. This study aimed to evaluate the encapsulation efficiency as well as morphological, physical, and chemical properties of encapsulated albumin using arrowroot porous starch. The P-50, porous starch:gum arabic (50:50) formula demonstrated the highest encapsulation efficiency of 98.88 %. Scanning electron microscopy revealed that porous starch adsorbs albumin on its surface. X-ray diffraction and Fourier-transform infrared profiles indicated an amorphous structure with minimal crystallinity, confirming the adsorption of albumin onto porous starch. The water content and water activity values of powder encapsulated with porous starch were better than those of native starch. Therefore, porous starch from arrowroot can be effectively used as an albumin encapsulant.